Deformation and Fracture Behavior of Sandwiched Copper Foam Brazed Joint Using Amorphous Copper–Tin–Nickel–Phosphorus Filler - Mohd Zahri, Nur Amirah; Yusof, Farazila; Badruddin, Irfan Anjum; Haseeb, A. S. Md. Abdul; Sukiman, Nazatul Liana; Kamangar, Sarfaraz (Frontiers in Materials, 2021)
Utilization of open-cell metal foams in functional applications such as in energy absorption, noise absorber, heat insulator, and lightweight panels is trending in many industrial applications. The development of reliable joining technologies for sandwiched metal foams is crucial for thermal application and one of the techniques used is brazing process. In the current work, copper foam was sandwiched between a copper plate using amorphous filler of Cu-9.7Sn-5.7Ni-7.0P (Cu: copper, Sn: tin, Ni: nickel, and P: phosphorus) via brazing technique. The shear test was conducted on the brazed joint interface of copper/copper foam, while the compressive test was carried out on the brazed sample. Microstructures of the copper substrate surface obtained from the shear fracture of brazed copper/copper foam show the tear region and cleavage fractures. The stress–strain curve of shear and compressive strength explains the deformation behavior of the brazed sample.